Systemes hamiltoniens k-symplectiques - Awane, Azzouz; Belam, Mohamed; Fikri, Sadik; Lahmouz, Mohammed; Naanani, Bouchra (Revista Matemática Complutense, 2002)
We study some properties of the k−symplectic Hamiltonian systems in analogy with the well-known classical Hamiltonian systems. The integrability of k−symplectic Hamiltonian systems and the relationships with the Nambu’s statistical mechanics are given.